2015
DOI: 10.1097/jto.0000000000000648
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Failure Analysis in Metastatic EGFR-Mutant Lung Cancer Treated with Tyrosine Kinase Inhibitors to Identify Candidates for Consolidation Stereotactic Body Radiation Therapy

Abstract: Initial progression of TKI-treated cancers occurred predominantly in original disease sites. Consolidation SBRT was judged feasible in a subset of patients following maximum TKI response and may have prevented oligoprogression in most of these. In addition, we hypothesize that consolidation SBRT for residual disease could delay subsequent metastatic reseeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 40 publications
3
79
1
Order By: Relevance
“…al., we find the predominant pattern of failure in our patients is within existing sites of disease, and that at two years, the cumulative incidence of such failure is over 50%, compared to a much smaller incidence of new- or combined-site failure. 17 Younger age and lack of initial CNS involvement are both associated with ISF. Greater intrathoracic primary disease burden is associated with progression, and intrathoracic progression is the sole site of initial failure in nearly a third of patients that experience ISF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al., we find the predominant pattern of failure in our patients is within existing sites of disease, and that at two years, the cumulative incidence of such failure is over 50%, compared to a much smaller incidence of new- or combined-site failure. 17 Younger age and lack of initial CNS involvement are both associated with ISF. Greater intrathoracic primary disease burden is associated with progression, and intrathoracic progression is the sole site of initial failure in nearly a third of patients that experience ISF.…”
Section: Discussionmentioning
confidence: 99%
“…Though several small reports of oligometastatic progression of oncogene-addicted NSCLC treated with local therapy have shown promising results, 1315 only two studies to our knowledge have evaluated the pattern of failure in metastatic patients treated with TKIs—one from a group of molecularly unselected patients and one from a relatively small set of EGFRmt patients treated with TKI. 16, 17 In both, half or more of the patients had progression limited to their initial sites of disease. Using a larger cohort of molecularly-selected EGFRmt patients treated with erlotinib, we sought to further characterize the frequency with which such patients progress in their initial sites of disease, and identify potential subsets of patients most likely to exhibit this pattern and therefore, potentially benefit from early local therapy.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been postulated that approximately 14-17% of patients with EGFR mutant NSCLC present with isolated CNS progression after front line treatment with EGFR TKIs (34)(35)(36)(37). However, others have demonstrated a lower incidence of BM in the same population (38). In a retrospective report by Heon et al, patients with EGFR mutant NSCLC treated with front line erlotinib and gefitinib had a lower rate of CNS progression compared with patients treated with chemotherapy [21% vs. 32% at 1 year, HR =0.56; 95% confidence interval (CI), 0.34-0.94] (39).…”
Section: Egfr Tkismentioning
confidence: 98%
“…Oligoprogression can include regrowth in metastatic sites and/or the lung primary. Perhaps surprisingly, a paucity of data is available on the patterns of regrowth when acquired drug resistance develops in oncogene-driven NSCLC [43]. We studied a cohort of EGFR-mutant patients and found that about half of recurrences after EGFR-targeted therapy occur first in the primary or pre-existing metastatic sites [43].…”
Section: The Concept Of Oligoprogressionmentioning
confidence: 99%